Advanced Finite Element Simulation of Ductile Structural Steel Incorporating a Crack Growth Model. (August 2018) - Hassan, M.S.; Salawdeh, S.; Goggins, J.
Abstract: A design methodology that addresses the modelling of ductile steel behaviour in a unified format is presented. In this methodology, three empirical laws defined as Hook's Law, Hollomon Law, Modified Weighted Average Law and a crack driven law based on the extended finite element method (XFEM) are linked empirically and systematically to format an advanced design approach. A set of test data representing forty-five coupon tests of 40 × 40 × 2.5, 20 × 20 × 2.0, and 50 × 25 × 2.5 (mm) square and rectangular steel hollow sections is used to demonstrate its applicability and effectiveness in driving the material model. The material model developed is employed in a robust numerical model of the steel hollow sections. Another set of data representing twenty-three monotonic static tests of steel hollow sections is employed to validate the XFEM model's performance. The XFEM results are found to match the physical tests values relatively well. In other words, when comparing the ratio of yield force, ultimate displacement, and energy dissipation capacity estimated from the finite element (FE) model to the measured values in the physical test, the mean values are found to be 1.03, 1.08, and 1.05 with a coefficient of variation of 0.05, 0.19, and 0.19, respectively. Hence, the design methodology presented and the XFEM model developed can be used with confidence as they have been calibrated and validated using the test data.